Organizations, decision making and strategy: Overview and comment - Cyert, Richard M.; Williams, Jeffrey R. (Strategic Management Journal, 1993)
In this overview to the Strategic Management Journal Winter 1993 Special Issue, we comment on the relationship between organization theory, strategy and decision making, and we review the contributions to this theme by our distinguished panel of authors. What is distinctive about strategic decisions? How does the organization function as an information processing mechanism? What information is strategic; when does information become strategic; and how do decision bias and locus affect competitive outcomes? How do process and structure, decision criteria, the layering of decisions, and domestic vs. global considerations affect performance? What is the role of beliefs and expectations; how do organizations effect proactive, creative behavior to recast their strategic decision patterns?